PENGARUH PERTUMBUHAN PENJUALAN DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Pramawati, Anak Agung Istri Anom Bintang; Darmayanti, Ni Putu Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024DO - 10.24843/EEB.2024.v13.i08.p09, 2024)
This research aims to determine the effect of sales growth and business risk on capital structure with profitability as a moderating variable. The population of this research is all food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period, totaling 49 companies using a saturated sample as sample determination. The method used in this research uses the observation methodthey do not participate. Data that has extreme values ??oroutlier 29 companies were obtained with an observation period of three years, resulting in 87 observations. The analysis technique used in this research is Moderated Regression Analysis (MRA). The analysis results show that sales growth has an insignificant positive effect on capital structure, while business risk has a significant negative effect on capital structure. The results of this research also found that profitability was unable to moderate the influence of sales growth on capital structure, while profitability was able to moderate the influence of business risk on capital structure. The implication of this research is that it is able to provide empirical evidence and is able to provide information to companies by paying attention to the factors that influence capital structure.